(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
After a period of massive use into the industrial production of plastic and synthetic materials, the trends are once again directed to natural materials and wood holds the championship in this respect. The variety of timber applications in design for children is large. There are huge series of products as well as limited series and unique ones. In the most of the designer developments is clearly visible the desire to focus on sustainable design searches. The report is an attempt to explore the possibilities for sustainable use of wood in the context of the increased criteria for harmlessness and safety as well as to address the extent to which these two aspects are complementary or opposing.